PENCANTUMAN LABEL HALAL PADA PRODUK MAKANAN RUMAHAN BERDASARKAN UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL DI KOTA PEKANBARU - Rany Angraini; Zulfikar Jayakusuma; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The application of halal labels on home-cooked food products in the city of Pekanbaru is still not running optimally. The reality is that there are still many home-cooked food products that are not halal-certified. In fact, Law Number 33 of 2014 concerning Halal Product Guarantee has stipulated this. The purpose of writing this thesis: first, to find out the application of halal labels to home-cooked food products based on law number 33 of 2014 concerning halal product guarantees in the city of Pekanbaru. Second, the legal consequences for producers who do not include halal labels on home-cooked food products based on law number 33 of 2014 concerning guarantees for halal products in the city of Pekanbaru.From the results of the study, the application of halal labels to home-cooked food products in the city of Pekanbaru is divided into several provisions, first, the application of halal labels to home-cooked food can be said to have not been implemented optimally. The absence of an obligation for business actors to register for halal certification is a separate gap for not agreeing to this. If we look further, the business actors who are the sample in this study are classified as middle and upper business actors and have above average income. Materially, of course, it does not become an obstacle for them to register for halal certification. The halal guarantee law only regulates the application of halal labels for business actors who have obtained halal certification, not on the obligation of business actors to register halal certification. There is no obligation for business actors to register the halal label itself. Second, the legal consequences for producers who do not include halal labels on home-cooked food products based on Law Number 33 of 2014 concerning Guaranteed Halal Products in the city of Pekanbaru can be said to have not run optimally. This is because there are no special provisions regarding legal consequences for business actors who do not register halal certification on the food packaging produced. Keywords: Halal Label – Business Actor - Consumer